INFLUENCE OF SOME PLANT WATER EXTRACTS ON THE GERMINATION AND SEEDLING GROWTH OF BARNYARD GRASS (ECHINOCHOLA CRUS-GALLI (L.)BEAUV) - Irshad, Aamer; Cheema, Zahid Ata (Biological Sciences - PJSIR, 2004)
Water extracts of rice husk (Oryza sativa L.), above ground foliage of barnyard grass (Echinochola crus-galli (L.) Beauv) and sorghum stalk (Sorghum bicolor L.) were used to investigate their allelopathic effects on the germination and seedling growth of barnyard grass in a laboratory study. All the water extracts exhibited suppressive effects on the germination and seedling growth of barnyard grass. The order of suppression was rice > sorghum barnyard grass. Regression analysis showed that better germination had the beneficial effect on the later growth of the seedling.